Optimization of Digital Marketing in Improving Marketing Performance - Herman, Bahtiar; Saleh, Wahyuni; Mursalat, Aksal (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
In the evolving era of digitalization, Majelis Ekonomi Perserikatan Muhammadiyah Sidenreng Rappang faces significant challenges in optimizing the utilization of its assets and adopting digital technology in its marketing strategies. This research aims to identify and develop effective digital marketing strategies to optimize the management of the organization’s assets, including rice commodities. Using a SWOT analysis, this study identifies the strengths, weaknesses, opportunities, and threats faced by the organization. The SWOT analysis results in 12 alternative strategies, which are then evaluated using the Quantitative Strategic Planning Matrix (QSPM) to determine the priority strategies. The research findings indicate that the primary strategies Majelis Ekonomi Perserikatan Muhammadiyah Sidenreng Rappang should adopt are leveraging community connections to increase internet usage and digital marketing for rice commodities, optimizing community connections to build competitive advantages, and collaborating with local businesses to overcome resource limitations. These findings position the organization in Quadrant 1 of the strategy matrix, supporting the implementation of aggressive strategies to maximize opportunities and address existing challenges. This research provides valuable insights for the organization in designing and implementing effective digital marketing strategies to achieve its economic and social objectives.